Political Communication on the Net: The trend to political “infotainment” in YouTube - Berrocal Gonzalo, Salomé; Campos Domínguez, Eva; Redondo García, Marta (Estudios sobre el Mensaje Periodístico, 2012)
This research focuses in the study of political infotainment. Originally, this is a genre linked to television, but now it is present in other media as Internet. This paper proves that many political videos of YouTube satisfy the characteristics of infotainment. Specifically, this paper shows the results of an analysis of the most played videos in YouTube in 2010 of of some representatives of European policy as Nicolas Sarkozy (France), Silvio Berlusconi (Italy), Gordon Brown (United Kingdom) or José Luis Rodríguez Zapatero (Spain), as well as the USA President Barack Obama (EEUU).